SURİYELİ SIĞINMACILARIN YERLEŞİM YERİ SEÇİMİNDE İL İSTİHDAM OLANAKLARINA VE ÖNCÜL SIĞINMACILARA DUYARLILIK MUKAYESESİ (Third Sector Social Economic Review, 2019)
The study focuses on the comparison of Syrian refugees’  formal employment in the cities and sensitiveness for previously refugee existence. Statistical data on the number of Syrian refugees were obtained from the directorate general of migration management. The formal employment data according to cities in 2016 is taken from the statistical yearbook of the SSI. Atkinson regional inequality index approach was used as a method of application. According to the findings, in 2016 the level of social utility from the distribution of additional refugees in nine cities with temporary shelter centers surpasses 85%, but compared with employment it regresses 70’ s%.  These rates, compared to previously refugees surpasses 60%, but compared to employment it changes between 21% and 29% in 70 cities without temporary shelter centers. Based on all 79 cities social utility ratio from premise refugees is 53%, social utility supplied from employment changes between 24% and 35%. The findings, support the idea that, according to the all cities with or without temporary shelter centers, previously Syrian existence has a powerful role compared to formal employment opportunities in cities for the settlement decision of the next migration flow.
Keywords: Social politics; sociology of work; labor economics; sociology of migration; economics and social demography.